New Insights Into the Local Auxin Biosynthesis and Its Effects on the Rapid Growth of Moso Bamboo (Phyllostachys edulis) - Bai, Yucong; Cai, Miaomiao; Mu, Changhong; Cheng, Wenlong; Zheng, Huifang; Cheng, Zhanchao; Li, Juan; Mu, Shaohua; Gao, Jian (Frontiers in Plant Science, 2022)
Auxin plays a crucial regulatory role in higher plants, but systematic studies on the location of auxin local biosynthesis are rare in bamboo and other graminaceous plants. We studied moso bamboo (Phyllostachys edulis), which can grow up to 1 m/day and serves as a reference species for bamboo and other fast-growing species. We selected young tissues such as root tips, shoot tips, young culm sheaths, sheath blades, and internode divisions for local auxin biosynthesis site analysis. IAA immunofluorescence localization revealed that auxin was similarly distributed in different stages of 50-cm and 300-cm bamboo shoots. Shoot tips had the highest auxin content, and it may be the main site of auxin biosynthesis in the early stage of rapid growth. A total of 22 key genes in the YUCCA family for auxin biosynthesis were identified by genome-wide identification, and these had obvious tissue-specific and spatio-temporal expression patterns. In situ hybridization analysis revealed that the localization of YUCCA genes was highly consistent with the distribution of auxin. Six major auxin synthesis genes, PheYUC3-1, PheYUC6-1, PheYUC6-3, PheYUC9-1, PheYUC9-2, and PheYUC7-3, were obtained that may have regulatory roles in auxin accumulation during moso bamboo growth. Culm sheaths were found to serve as the main local sites of auxin biosynthesis and the auxin required for internode elongation may be achieved mainly by auxin transport.